Effect of Work Discipline and Employee's Motivation on Employee's Work Performance in the Proclamation Manuscript Formulation Museum with Communication as an Intervening Variable - Emir Fikri Herdani; Masydzulhak Djamil (Journal of Accounting and Finance Management, 2022)
This study aims to determine the direct or indirect effects between motivational variables and work discipline variables on performance variables and another objective is to find the independent variable that has the most influence on the performance variable. The subjects of the study were 40 employees of the Proclamation Manuscript Formulation Museum. Questionnaires were used to collect data, which were then analyzed using multiple linear analyses. The results indicate that motivation and work discipline have a significant direct influence on communication. Motivation and work discipline have a significant direct effect on performance. Motivation and work discipline had a significant indirect impact on performance with communication as an intervention variable. To improve work efficiency, it is necessary to improve motivation and work discipline, because work efficiency will increase with the increase and flourishing of motivation and working environment.